Present fatty acid identification in oil extracted of seeds of soursop (Annona muricata) - Cerón C, Andrés Felipe; Osorio M, Oswaldo; Hurtado B, Andrés (Revista de Ciencias Agrícolas, 2012)
The objective of the present study was to determine the yield in oil and the present fatty acids in the oil obtained from seeds of soursop (Annona muricata), provided by the company (INPADEMA) in the municipality of Pasto (Nariño), the extraction I carry out by means of the Soxhlet Extractor using like reliable ethylic ether of boiling point 40-60 ºC, to identify present fatty acids use gas chromatography GC-FID, obtained a yield of 30,59% in oil, as far as the fatty acid composition was: palmitic 29,60%; stearic 5,89%; oleic 33,47%; linoleic 27,77% and linolénico 3,28%. It was determined that 35,49 % of the fatty acids are saturated and 64,51% are mostly unsaturated and may be of great interest in the different industry.